Effect of Al-Doping on Electrochemical Performance of LiMn2O4 - Liang, Xinghua; Zeng, Shuaibo; Liu, Yusi; Liu, Tianjiao; Shi, Lin; Ye, Chaochao (Asian Journal of Chemistry, 2014)
Spinel LiMn2O4 and LiAlXMn2-XO4(GX, X = 0, 1, 2, 3, 4) have been synthesized by solid-state method. The synthesized samples were characterized by following methods: X-ray diffraction, scanning electron microscopy. Results showed that LiAl0.3Mn1.7O4(G3) was spinel structure which space group was Fd3m. The spinous substances were not observed on its spherical-structured surface. Experimental battery EX(X = 0, 0.1, 0.2, 0.3, 0.4) was assembled by using GX as cathode electrode, active carbon as conductive agent and Li plate as the anode electrode. The EX(X = 0, 0.1, 0.2, 0.3, 0.4) was characterized by electrochemical impedance spectroscopy, cyclic voltammetry and charge-discharge studies. Results indicated that Al-substitution decreased the internal resistance of EX. Charge-discharge cycling studies and cyclic voltammetry test showed that Al-substitution substantially improved the capacity retention of the EX.